1983
DOI: 10.1007/bf01460004
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated paraffins: Disposition of a highly chlorinated polychlorohexadecane in mice and quail

Abstract: Uniformly 14C-labelled 1-chloro-polychlorohexadecane (PCHD) of high chlorine content (69% w/w) was given to Japanese quail and to C57Bl mice perorally (p.o.) and intravenously (i.v.). The degradation of PCHD to 14CO2, measured during 8 h, was found to be minute (about 1% of dose) in both species after either route of administration. In mice 66 and 43% of dose was eliminated in the feces during 96 h following p.o. and i.v. administration, respectively; the urinary excretion was about 3% in both cases. In quail,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…For the low chlorinated MCCP (Darnerud and Brandt, ), about 33% of the administered radioactivity was exhaled as 14 CO 2 within 12 h after oral administration with 6.5% of the radioactivity in the urine and 14% in the faeces. For the higher chlorinated MCCP (Biessmann et al., ), the elimination of radioactivity in urine was about 3% and about 66% in the faeces during 96 h; the elimination in exhaled air was about 1%.…”
Section: Assessmentmentioning
confidence: 98%
See 3 more Smart Citations
“…For the low chlorinated MCCP (Darnerud and Brandt, ), about 33% of the administered radioactivity was exhaled as 14 CO 2 within 12 h after oral administration with 6.5% of the radioactivity in the urine and 14% in the faeces. For the higher chlorinated MCCP (Biessmann et al., ), the elimination of radioactivity in urine was about 3% and about 66% in the faeces during 96 h; the elimination in exhaled air was about 1%.…”
Section: Assessmentmentioning
confidence: 98%
“…In the elimination part of the study with the SCCP and the lower chlorinated MCCP (Biessmann et al., ), the exhalation of 14 CO 2 during 8 hours following dosing with the MCCP was about twice (38.8%) that of the SCCP (21.6%); the excretion of radioactivity in urine and faeces (combined, during 8 hours) was also higher following dosing with the MCCP (13.5%) compared with SCCP (9.8%). For the higher chlorinated MCCP (Biessmann et al., ), the elimination of radioactivity in urine and faeces (combined) was about 58% during 96 hours after administration; the elimination in exhaled air was about 1%.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 5000 mg/kg b.wt./day of a long chain, 43% chlorinated CP administered to rats on day 6-19 of gestation gave no increase in the frequency of foetal anomalies. However, in an earlier study we observed a strong accumulation of a highly chlorinated I4C-hexadecane in the ovaries of non-pregnant mice (Biessmann et al 1983). It was therefore of interest to study if a similar chloroalkane (this time unlabelled and in a higher dose) has any effect on the implantation and embryonic development in mice.…”
mentioning
confidence: 89%